Long-lived domain wall plasmons in gapped bilayer graphene - Hasdeo, Eddwi H. (2019)
Topological domain walls in dual-gated gapped bilayer graphene host edge states that are gate-tunable and valley polarized. Here we predict that plasmonic collective modes can propagate along these topological domain walls even at zero bulk density and possess a markedly different character from that of bulk plasmons. Strikingly, domain wall plasmons are extremely long-lived with plasmon lifetimes that can be orders of magnitude larger than the transport scattering time in the bulk at low temperatures. Importantly, long domain wall plasmon lifetimes persist even at room temperature with values up to a few picoseconds. Domain wall plasmons possess a rich phenomenology including plasmon oscillation over a wide range of frequencies (up to the mid-infrared), tunable subwavelength electromagnetic confinement lengths, as well as a valley polarization for forward/backward propagating modes. Its unusual features render them as a new tool for realizing low-dissipation plasmonics that transcend the restrictions of the bulk.